AcrIF9 tethers non-sequence specific dsDNA to the CRISPR RNA-guided surveillance complex - Marscha Hirschi (Nature Portfolio, 2020)
The anti-CRISPR protein IF9 (AcrIF9) specifically inhibits the type I-F CRISPR adaptive immune system. Here, the authors present the cryo-EM structure of AcrIF9 in complex with the type I-F CRISPR RNA-guided surveillance complex (Csy) and a dsDNA bound Csy-AcrIF9 structure, and find that AcrIF9 binding to the Csy complex triggers non-sequence specific dsDNA binding to Csy-AcrIF9, which might sequester the complex from its target DNA.